SISTEM PENGONTROLAN LAMPU MENGGUNAKAN INTERFACE ARDUINO VIA USB DI HOTEL NUGRAHA MALANG - Muhammad Muchlis; Linda Suvi Rahmawati (Sekolah Tinggi Manajemen Informatika & Komputer PPKIA Pradya Paramita Malang, 2023)
One way the use of appropriate electrical or electrical energy savings that is by turning off unused electrical appliances , and one of them is the use of lighting as needed and situations .Based on the observations made on the use of light in several rooms the hotel room can be concluded that the presence of waste in the use of electrical energy . This is due to the behavior and human consciousness that room users who tend to not care or are oblivious to the electricity saving measures . The lights in the room are often seen stays on even when not used . In other words , the lights in the room are seen constantly in the room lit though no one . To avoid the use of information that is not appropriate , it required an ignition system and lights are controlled shutdown .